Anthills: stressor or opportunity for plant assemblage diversity? Evidence from Mediterranean Dasypyretum grasslands. Issue 4 (4th July 2022) - Battisti, Corrado; Di Giulio, Andrea; Fanelli, Giuliano; Cerfolli, Fulvio
Abstract : We explored the structure of plant assemblages that settles around the anthills of a guild of Hymenoptera Formicidae ( Messor wasmanni Krausse 1910, Tapinoma nigerrimum Nylander 1856 and Aphaenogaster spinosa Emery 1878), observable in urban grasslands dominated by Dasypyrum villosum (Rome, Central Italy). Since it is known that ants act as a disturbing factor on plant assemblages of grasslands, our hypothesis was that vegetation structures suffer from some stressors that affect, in this plant association, the dominant plant structure. We compared the plant assemblages observed in the plots of the anthills with the control grassland assemblages using a diversity/dominance diagram. We recorded 63 plant taxa. The average number of plant species was found to be significantly lower in anthill plots than in control grassland plots. In anthill plots, dominant plant species ( Polygonum romanum, Poa trivialis Vulpia myuros, Aira elegantissima and Vulpia ligustica ) have been found to be different from control grassland plots ( Convolvolus arvensis, Dasypyrum villosum, Poa trivialis and Sheradia arvensis ). Anthill plant assemblages were found to be significantly different (One-way PERMANOVA) and poorer in terms of species richness, less diversified, and with a reduced species turnover than control grassland plots. Whittaker plot analysis seems to show that the plant assemblages of the control, with greater evenness, emphasize a stressed condition in anthill plant assemblages. Non-metric multidimensional scaling shows a set of species strictly linked to anthills. Our data seem to confirm the role of ants as a stressor in the plant assemblage structures of Mediterranean urban grasslands. However, our results also show that the peculiar ant nest conditions may favor plant species less represented in the Dasypyretum grasslands (i.e. Polygonum romanum ) or even absent in this plant assemblage (i.e. Aira elegantissima, Cynodon dactylon and Poa annua ), thus increasing the overall local plant diversity.